The islet of Klissova and the church of Agia Triada in Mesologgi, Greece: a holistic approach - Παπουτσάκη, Αναστασία (Πανεπιστήμιο Πελοποννήσου, 2023)
The present MSc thesis focuses on the digitization, documentation, and preservation of the church of Agia Triada, which is located on the islet of Klissova, in the Mesologgi region, Greece. The primary objective of this research is to employ modern technologies to create an accurate 3D model of the site, while also investigating the construction materials and manufacturing techniques used in the preservation of the church. To accomplish these goals, the islet and church were meticulously documented using an Unmanned Aerial Vehicle (UAV) and Global Positioning System (GPS) technology. This approach facilitated the creation of a highly precise and detailed 3D model of the site, allowing for comprehensive virtual exploration and analysis. Furthermore, in order to conserve and preserve the church, specific construction materials, mortars and stones from the outer walls were carefully selected for subsequent laboratory analysis. The laboratory techniques employed in this study include LED microscopy, Scanning Electron Microscopy coupled with Energy- Dispersive X-ray Spectroscopy (SEM/EDS), grain size distribution analysis and X-ray Diffraction (XRD) analysis. These techniques were utilized to gain insights into the manufacturing technology of the mortars and to determine their composition and structural properties. The study reveals the chemical and mineralogical characteristics of the construction materials, including high-calcium lime mortars. The mortars exhibit a mixture of well-graded and gap-graded characteristics. Further analysis is needed to investigate the presence of plaster. The same analytical techniques were applied to samples from the exterior wall of Vasiladi islet for comparative reasons and for future research, showing similar results.
Keywords: Ναός Αγίας Τριάδας (Κλείσοβα, Νησί) -- Ελλάδα; Φωτογραμμετρία; Τρισδιάστατη απεικόνιση στην αρχαιολογία; Συστήματα απεικόνισης στην αρχαιολογία; Εκκλησίες -- Συντήρηση και αποκατάσταση -- Ελλάδα; Αρχαιολογία -- Μεθοδολογία -- Επεξεργασία δεδομένων; Κονίαμα -- Ανάλυση; Klissova; Church; Photogrammetry; Analytical techniques; Κλείσοβα; Εκκλησία; Φωτογραμμετρία; Αναλυτικές τεχνικές